Exploring the Causal Pathway From Telomere Length to Alzheimer’s Disease: An Update Mendelian Randomization Study - Gao, Kai; Wei, Chen; Zhu, Jin; Wang, Xin; Chen, Guoqing; Luo, Yangyang; Zhang, Dai; Yue, Weihua; Yu, Hao (Frontiers in Psychiatry, 2019)
Increasing evidence shows that telomere length shortening is associated with the risk for Alzheimer’s disease (AD), pointing to a potential modifiable target for prevention. However, the causality of this association is still not clear. To investigate the causal relationship between telomere length and AD, we use two-sample Mendelian randomization (MR) to assessing potential causal inference. We used summary-level data for telomere length (9190 participants) and AD (71,880 cases and 383,378 controls). We performed two-sample MR analysis with single nucleotide polymorphisms previously identified to be associated with telomere length. The MR analyses were conducted using the inverse-variance-weighted method and complemented with the maximum likelihood, weighted median, weighted mode approaches. MR evidence suggested that shorter telomere length was causally associated with a higher risk for AD (IVW estimate of odds ratio (OR): 1.03 per SD decrease of telomere length, P=1.21×10-2). The maximum likelihood, weighted median, weighted mode yielded a similar pattern of effects. The results were similar in sensitivity analyses. Using genetic instruments identified from large-scale GWAS, robust evidence supports a causal role of telomere length shortening with increased risk of AD.